Proposal for the use of angiotensin II in distributive shock after extracorporeal circulation – position paper of the Section of Intensive Care Medicine and the Section of Cardiothoracic Anaesthesiology of the Polish Society of Anaesthesiology and Intensive Therapy - Krzych, Łukasz; Nadziakiewicz, Paweł; Kucewicz-Czech, Ewa (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2024)
Angiotensin II (AT) is a potent vasoconstrictor and hypertensive drug that is registered for the treatment of severe hypotension in vasoplegic shock. Growing experience with the use of AT in cardiac surgery allows the first therapeutic algorithms to be created. This paper is a proposal for the use of AT in distributive shock after extracorporeal circulation.